The Path of Pleasantness Ippolito II d'Este Between Ferrara, France and Rome - Vidori, Giulia (Premio Istituto Sangalli per la storia religiosa, 2020)
Ippolito II d'Este (1509-1572), cardinal and prince of Ferrara, played a crucial role in shaping the political and cultural connections between Italy and France. Seen by his contemporaries as staunchly 'French', his life rather followed a difficult balance between the political and spatial entities - Rome, Paris, and Ferrara - through which he continuously moved and from which he derived his power. Following his career as cardinal protector of the Valois crown, royal administrator of Siena on behalf of Henry II, and papal legate to France on the eve of the Wars of Religion, this book argues that Ippolito's apparent diplomatic access ultimately weakened his family's position in Italy and left it ill-equipped to compete in the changing politics of the peninsula.